2010
DOI: 10.1080/15377931003760989
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Crime Among Chinese Immigrants

Abstract: This is an electronic version of an article published in Journal of Ethnicity in Criminal Justice, 8(2) AbstractWestern scholars implicitly assume that the correlates of fear of crime discovered in the extant literature are also applicable to populations of different culture and ethnic backgrounds. The current study investigates whether such an assumption is valid, drawing on survey data of Chinese immigrants in Houston. Among other findings, this study reveals that the effect of age on fear of crime is negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 38 publications
(62 reference statements)
3
36
2
Order By: Relevance
“…Second, the crime and justice model suggests that people's experience with crime and criminal justice agencies, particularly the police, is critical to their fear of crime. Some studies report that victimization is positively related to fear (Skogan and Maxfield, ; Yun, Kercher, and Swindell, ), while others indicate that groups with the lowest victimization rates (e.g., elderly women) harbor the greatest fear (Lee and Ulmer, ; Warr, ). Neither personal violent victimization nor property victimization are found to be significant correlates of Chinese fear of crime, after controlling for perceived neighborhood disorder (Liu, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, the crime and justice model suggests that people's experience with crime and criminal justice agencies, particularly the police, is critical to their fear of crime. Some studies report that victimization is positively related to fear (Skogan and Maxfield, ; Yun, Kercher, and Swindell, ), while others indicate that groups with the lowest victimization rates (e.g., elderly women) harbor the greatest fear (Lee and Ulmer, ; Warr, ). Neither personal violent victimization nor property victimization are found to be significant correlates of Chinese fear of crime, after controlling for perceived neighborhood disorder (Liu, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research has continuously demonstrated that victims of crime are more likely to have less favorable perceptions of police (Brown & Benedict, 2002;Cao et al, 1996;Carter, 1985;Geistman & Smith, 2007;Hurst & Frank, 2000;Vogel, 2011;Wu et al, 2009) and to be more fearful of crime than those who have not been victimized (Yun, Kercher, & Swindell, 2010). These issues are particularly salient considering it has been suggested Hispanics are disproportionally victimized (e.g.…”
Section: Contextual Variablesmentioning
confidence: 97%
“…In coming up with research variables this study was guided by most of the literatures from criminology studies, as they are the ones associated with in uence on safety and security issues, we opted to choose this way of thinking because literature indicates that IS belong to special minority group that are socially vulnerable by applying the vulnerability theory which has been used in many safety and security studies from all over the world [33][34][35] . Literature indicates that government policies, measures and actions are one of the major contributing factors that may in uence safety and security of the country in general at a national level and of its citizen, furthermore, the policies may also in uence foreigners safety and security perceptions in times of wars, epidemics and pandemics or any disasters 24,[36][37][38] , to the extents that if well implemented and followed they may even reduce the spread of pandemics like of that of COVID-19 infectious disease 38 .…”
Section: Research Variablesmentioning
confidence: 99%
“…The other variables of the study were (i) gender where the literatures indicates that male have higher safety perception as compared to female, (ii) age where old people have high safety perception than younger ones, (iii) education level where those with high education level have high safety perception than those with low education levels, (iv) length of stay, where those that have more stayed have higher safety perceptions as compared with those with no more experience, (v) marital status where the literature indicates that those that are married have higher safety perception as compared to those that are not married 34,41,46,47 , (vi) regional comparison, where the literature has indicated that even a location where people are located with an area, i.e. those that may be close to military base may feel high security than others, those that are located far from pandemics starts points may have higher security perception than others 30,41,48 .…”
Section: Characteristics Of People In the Studymentioning
confidence: 99%